An elastography method based on the scanning contact resonance of a piezoelectric cantilever. Issue 12 (12th November 2013) - Fu, Ji; Li, Faxin
Abstract : Purpose: : Most tissues may become significantly stiffer than their normal states when there are lesions inside. The tissueˈs modulus can then act as an identification parameter for clinic diagnosis of tumors or fibrosis, which leads to elastography. This study introduces a novel elastography method that can be used for modulus imaging of superficial organs. Methods: : This method is based on the scanning contact‐resonance of a unimorph piezoelectric cantilever. The cantilever vibrates in its bending mode with the tip pressed tightly on the sample. The contact resonance frequency of the cantilever‐sample system is tracked at each scanning point, from which the sampleˈs modulus can be derived based on a beam dynamic model and a contact mechanics model. Scanning is performed by a three‐dimensional motorized stage and the whole system is controlled by a homemade software program based on LabVIEW. Results: : Testing on in vitro beef tissues indicates that the fat and the muscle can be easily distinguished using this system, and the accuracy of the modulus measurement can be comparable with that of nanoindentation. Imaging on homemade gelatin phantoms shows that the depth information of the abnormalities can be qualitatively obtained by varying the pressing force. The detection limit of this elastography method is specially examined both experimentally and numerically. Results show that it can detect the typical lesions in superficial organs with the depth of several centimeters. The lateral resolution of this elastography method/system is better than 0.5 mm, and could be further enhanced by using more scanning points. Conclusions: : The proposed elastography system can be regarded as a sensitive palpation robot, which may be very promising in early diagnosis of tumors in superficial organs such as breast and thyroid.